“Don’t Change Yourselves": International Students’ Concepts of Belonging at a Liberal Arts College - Bjork, Christopher; Abrams, Anna; Hutchinson, Lilia S.; Kyrkjebo, Nora I. (Journal of International Students, 2020)
While international students face many similar challenges, regardless of their location of study, the unique aspects of learning institutions may lead to different outcomes. Cognizant of this situation, we conducted a study designed to analyze the experiences of 28 students attending an undergraduate liberal arts college. The comments expressed by our informants underscore the sense of agency students developed as they responded to challenging circumstances that did not always recognize their unique perspectives. The subcultures they formed with other international students helped them adjust to their new surroundings without feeling obligated to discard unique aspects of themselves. Although the lived experiences of the students we interviewed rarely matched the images they carried with them when they matriculated, their comments indicated that they ultimately achieved of their goals for studying abroad. These findings offer insights into the identities and experiences that are often overlooked in research on international education.